Herbal products: utilization, knowledge and attitudes of Turkish adults - Yilmazel, Gülay; Naçar, Melis (International Journal of Basic & Clinical Pharmacology, 2016)
Background: This study was aimed to determine utilization, knowledge and attitudes of Turkish adults on herbal products. Methods: This cross-sectional study was conducted in a Turkey city-Çorum with 600 adults aged between 18-85 during June 2015. A self-administered questionnaire was used to collect data on demographics, and general knowledge, experiences and attitudes about herbal products. Results: Of these responses, 67.3% of were women and 32.7% were men; 34.7% were aged 35-49 years with the mean age of 33.7. The 14.2% had any chronic disease and of these 38.8% were suffering from cardiovascular disease and hypertension. The overall utilization of herbal products was 55.7%. Most common health issues treated via HPs by respondents were found to be intestinal illness and losing weight. Responses had predominantly negative but sophisticated attitudes towards to herbal products. Women were more likely to be users with the increased risk of 1.9 times higher than men. Also family size, chronic conditon and current medication use were significant predictors of herbal produts use. Herbal product use was significantly higher in responses who had “moderate-bad” health perception. Among the attitudes, attitude -7 and attitude -11 were the other strongest factors on herbal product use. Conclusions: The present study confirms previous findings and provides additional evidence that using herbal products among Turkish adults is still prevalent with the lack of information and semi-positive attitudes.